2022
DOI: 10.1136/bmjopen-2021-059408
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on utilisation of facility-based essential maternal and child health services from March to August 2020 compared with pre-pandemic March–August 2019: a mixed-methods study in North Shewa Zone, Ethiopia

Abstract: IntroductionHealth systems are often weakened by public health emergencies that make it harder to access health services. We aimed to assess maternal, newborn and child health (MNCH) service utilisation during the first 6 months of the COVID-19 pandemic compared with prior to the pandemic.MethodsWe conducted a mixed study design in eight health facilities that are part of the Birhan field site in Amhara, Ethiopia and compared the trend of service utilisation in the first 6 months of COVID-19 with the correspon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
65
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 26 publications
(27 reference statements)
0
65
0
Order By: Relevance
“… Bekele C., Bekele D., Hunegnaw B.M., et al, 2022. Ethiopia [ 8 ] Assess MNCH utilization during the first six months of the COVID-19 pandemic, as well as potential barriers and enablers of service utilization from health care providers and clients. Mixed study design.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Bekele C., Bekele D., Hunegnaw B.M., et al, 2022. Ethiopia [ 8 ] Assess MNCH utilization during the first six months of the COVID-19 pandemic, as well as potential barriers and enablers of service utilization from health care providers and clients. Mixed study design.…”
Section: Resultsmentioning
confidence: 99%
“…Movement restrictions and transport challenges were also identified as barriers to maternal health service uptake in Ethiopia [ 8 , 14 ]. Similarly, the findings of cross-sectional survey of 1241 Nigerian women by Balogun et al, [ 25 ] and a mixed method study in Ethiopia [ 8 ] showed that lockdowns and lack of transportation were barriers to accessing MHC services.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations